A Case Report of Statin-Induced Immune-Mediated Necrotizing Myopathy Treatment Challenges - Joudeh, Anwar I.; Albuni, Mhd Kutaiba; Hassen, Sara Seife; Iqbal, Phool; Aziz Bedair, Elsaid Mohamed; Mahdi, Salah (Case Reports in Rheumatology, 2022)
Statin-induced necrotizing autoimmune myopathy is an immune-mediated necrotizing myopathy related to the use of statins. It is a very rare disease, which usually presents with proximal muscle weakness and frank elevation in creatine kinase levels. Stopping statin and the use of immunosuppressive therapy are considered the mainstay therapy. Use of steroids in patients with inflammatory myopathy can be complicated by steroid-induced myopathy. Herein, we present a case of a 55-year-old patient with statin-induced necrotizing autoimmune myopathy based on the presence of proximal muscle weakness, magnetic resonance findings, suggestive muscle biopsy features, and positive anti-HMGCR autoantibodies. The patient was treated with triple immunosuppressive therapy with a particularly good response to intravenous immunoglobulin. This report highlights the importance of timely diagnosis and early use of combined immunosuppressive therapy to improve patients’ outcome affected by this rare disease.